2023
DOI: 10.1101/2023.02.13.23285859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Poor sleep quality, insomnia, and short sleep duration before infection predict long-term symptoms after COVID-19

Abstract: Study objectives: Millions of COVID-19 survivors experience a wide range of long-term symptoms after acute infection, giving rise to serious public health concerns. To date, few risk factors for post-COVID-19 conditions have been determined. This study evaluated the role of pre-infection sleep quality/duration and insomnia severity in the incidence of long-term symptoms after COVID-19. Methods: This prospective study involved two assessments (April 2020 and 2022). At baseline, sleep quality/duration and insomn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…33 Our sleep quality measure combined the effects of both sleep efficiency and sleep duration, but exploratory analyses suggested that low and inconsistent sleep efficiency—which can reflect a range of sleep disturbances, such as increased sleep latency and fragmented sleep—was driving the relationship observed. This is in line with other studies, which have found increased risk of long COVID associated with pre-infection sleep disturbances, 911 whereas results on sleep duration are inconsistent 9,10 and do not always consider the simultaneous effect of sleep efficiency. 35 Together, these findings suggest short sleep duration, on its own, is unlikely to substantially increase the risk of long COVID; instead, the focus should be on ensuring consistently good-quality sleep to aid recovery from future infections.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…33 Our sleep quality measure combined the effects of both sleep efficiency and sleep duration, but exploratory analyses suggested that low and inconsistent sleep efficiency—which can reflect a range of sleep disturbances, such as increased sleep latency and fragmented sleep—was driving the relationship observed. This is in line with other studies, which have found increased risk of long COVID associated with pre-infection sleep disturbances, 911 whereas results on sleep duration are inconsistent 9,10 and do not always consider the simultaneous effect of sleep efficiency. 35 Together, these findings suggest short sleep duration, on its own, is unlikely to substantially increase the risk of long COVID; instead, the focus should be on ensuring consistently good-quality sleep to aid recovery from future infections.…”
Section: Discussionsupporting
confidence: 90%
“…Our use of prospectively collected, pre-infection sleep data strengthens our estimates of pre-infection sleep; most studies to date have relied on retrospectively reported pre-infection sleep data, 3,32,35,37,38 and research has shown that people asked to retrospectively recall their sleep before the pandemic estimated that they slept much better than they actually did. 6 Our extended follow-up enabled us to capture long COVID symptoms presenting at any point after infection, and to record sleep duration over the entire year after infection, in contrast with other studies that have relied on a cross-sectional approach, 32,37 infrequent assessments, 10 or shorter follow-up. 38 Monthly responses from our participants meant that we were able to track changes in sleep duration with detail that would have been missed if observations had been further apart, while simultaneously allowing us to adjust for time-varying factors that may affect people's sleep habits-particularly in the context of a pandemic that limited people's movement and employment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower sleep quality, more severe insomnia, and shorter sleep duration 1 to 3 months post-COVID-19 are associated with higher odds of developing a wide range of clinical manifestations. Our findings suggest that the impact of sleep loss on vaccination effectiveness may mediate the link between sleep and post-COVID-19 symptoms[11]. Moreover, studies have reported the efficacy of various tea ingredients in blocking COVID-19 infection[28].…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, our results related to poor sleep quality are supported by data from the aforementioned Italian cohort study which showed that higher scores on the Pittsburgh Sleep Quality Index predicted a greater risk for developing symptoms associated with PASC. 25 Furthermore, in a study of 1,581 persons from the United Kingdom who were surveyed concerning their sleep quality one month before their COVID-19 infection, persons who reported average to very poor sleep quality were 2.4-3.5 times more likely to self-report having "Long COVID". 24 Our study extends these June 12, 2024 previous observations by using a more precise definition of poor sleep quality as well as a more formal definitions of PASC.…”
Section: Discussionmentioning
confidence: 99%